Wstęp do badań nad diecezją Nola w XVII wieku - Fitych, Tadeusz (Archiwa, Biblioteki i Muzea Kościelne, 2009)
The author is known in Poland by his many works, as, for example, the history and organization the Polish Nuncio’s office, and the history, the culture and theology of Silesia. He also promises to extend his research into the implementation of the reform resolutions of the Council of Trent in the diocese of Nola, one of the most prestigious dioceses in Italy. The origins of this diocese coincide with the very origins of Christianity. Keeping in mind the vitality of that work as well as desiring to eliminate the gap caused by a lack of a monograph on the history of that local Church, the author presents both a brief overview of the history of the region, of Naples and the diocese of Nola itself, presenting its best known rulers, the history of the basilicas and bishop’s churches, as well as the state of the parishes until the early years of seventeenth century. To this end, the author has compiled a lengthy bibliography (over 180 titles of books and articles) published between the middle of seventeenth century and now. These works deal with the history of this region’s towns, its royal and ennobled houses, and also with its religious orders, institutions and most outstanding persons. Works from the areas of culture and art are also considered.